Investigating the physiological and metabolomic effects of Ecklonia maxima-derived biostimulant foliar application in ameliorating the effects of heat shock in tomato plants - Dladla, Unathi (Department of Molecular and Cell Biology, 2025)
Tomato (Solanum Lycopersicum) is a globally popular horticultural commodity with great economic importance and is highly susceptible to heat shock and heat stress. Heat shock has evidenced detrimental effects on plant viability and growth, limiting crop productivity and quality. In addition to physical damage, structural damage to plant cell walls and membranes and the overproduction of reactive oxygen species (ROS) also cause metabolic and cellular disturbances. Concurrently, there has been a growing demand for sustainable and affordable agricultural practices using eco-friendly approaches to increase the heat tolerance of crops. Biostimulants are substances or microorganisms that help improve plant growth, yield, nutrient content and quality and can also enhance plant tolerance to different abiotic stresses either as stress priming agents or mitigating the stress directly. In South Africa, commercial biostimulant manufacture is focused on the brown algae (Phaeophyta), Ecklonia maxima (Osbeck) which grows and is harvested along the southern Atlantic coast of Africa. In this study, the aim was to assess and determine whether the prior foliar application of Ecklonia maxima-derived biostimulant on tomato plants could assist in improving the tolerance of tomato plants to subsequent heat shock stress. The focus was on the physiological, biochemical and metabolic responses of tomato plants treated with or without E. maxima-derived biostimulant and subject to heat shock stress. This was achieved through different plant physiological and biochemical approaches that include electrolyte leakage assay, chlorophyll fluorescence and photosynthetic pigment measurements, FRAP (ferric reducing antioxidant power) and DPPH (2,2-diphenyl1-picrylhydrazyl) measurements and lipid peroxidation and proline assays. In addition, changes in the primary metabolites of the treated tomatoes were measured using gas chromatography mass spectrometry (GC-MS) to further elucidate the metabolic pathways involved in the responses to the different treatments. From the findings, it was shown that a prior foliar application of E. maxima-derived biostimulant resulted in better photosynthetic efficiency and a decrease in the amount of electrolyte leakage from plant cells when subsequently exposed to heat shock stress compared to control plants without prior biostimulant application. This indicates improved cell membrane integrity and enhanced thermotolerance of E. maxima treated plants in response to heat shock stress. There was also a reduction in lipid peroxidation and proline content in heat shocked plants treated prior with E. maxima-derived biostimulant, indicating enhanced ROS scavenging and antioxidant systems in these biostimulant treated plants. The metabolic analysis of the shoots from heat shocked plants that were prior treated with E. maxima-derived biostimulant identified key sugars, organic acids and amino acids. These included phenylalanine, valine, proline, threonine, myo-inositol, citric acid, mannitol, and succinic acid. The identified primary metabolites are linked to the promotion of plant growth by increasing chlorophyll content and mitigate stress by assisting in reducing the levels of ROS in plants and improving the antioxidant defence system. This study showed that the E. maxima-derived biostimulant acts as a priming agent to enhance and protect photosynthesis while improving thermotolerance to heat shock stress by directly and/or indirectly enhancing antioxidant capacity in the plants.